A Cytosol-Localized Geranyl Diphosphate Synthase from Lithospermum erythrorhizon and Its Molecular Evolution. Issue 4 (23rd January 2020) - Ueoka, Hayato; Sasaki, Kanako; Miyawaki, Tatsuya; Ichino, Takuji; Tatsumi, Kanade; Suzuki, Shiro; Yamamoto, Hirobumi; Sakurai, Nozomu; Suzuki, Hideyuki; Shibata, Daisuke; Yazaki, Kazufumi
Abstract : A unique cytosol-localized geranyl diphosphate synthase supporting a large production of shikonin has evolved from farnesyl diphosphate synthase in Lithospermum erythrorhizon. Abstract: Geranyl diphosphate (GPP) is the direct precursor of all monoterpenoids and is the prenyl source of many meroterpenoids, such as geranylated coumarins. GPP synthase (GPPS) localized in plastids is responsible for providing the substrate for monoterpene synthases and prenyltransferases for synthesis of aromatic substances that are also present in plastids, but GPPS activity in Lithospermum erythrorhizon localizes to the cytosol, in which GPP is utilized for the biosynthesis of naphthoquinone pigments, which are shikonin derivatives. This study describes the identification of the cytosol-localized GPPS gene, LeGPPS, through EST- and homology-based approaches followed by functional analyses. The deduced amino acid sequence of the unique LeGPPS showed greater similarity to that of farnesyl diphosphate synthase (FPPS), which generally localizes to the cytosol, than to plastid-localized conventional GPPS. Biochemical characterization revealed that recombinant LeGPPS predominantly produces GPP along with a trace amount of FPP. LeGPPS expression was mainly detected in root bark, in which shikonin derivatives are produced, and in shikonin-producing cultured cells. The GFP fusion protein in onion ( Allium cepa ) cells localized to the cytosol. Site-directed mutagenesis of LeGPPS and another FPPS homolog identified in this study, LeFPPS1, showed that the His residue at position 100 of LeGPPS, adjacent to the first Asp-rich motif, contributes to substrate preference and product specificity, leading to GPP formation. These results suggest that LeGPPS, which is involved in shikonin biosynthesis, is recruited from cytosolic FPPS and that point mutation(s) result in the acquisition of GPPS activity.